Simulation of Calcium Phosphate Pre-Nucleation Clusters in Aqueous Solution: Association Beyond Ion Pairing - Garcia, Natalya; Innocenti Malini, R.; Freeman, C.; Demichelis, Raffaella; Raiteri, Paolo; Sommerdijk, N.; Harding, J.; Gale, Julian (American Chemical Society, 2019)
© 2019 American Chemical Society. Classical molecular dynamics simulations and free energy methods have been used to obtain a better understanding of the molecular processes occurring prior to the first nucleation event for calcium phosphate biominerals. The association constants for the formation of negatively charged complexes containing calcium and phosphate ions in aqueous solution have been computed, and these results suggest that the previously proposed calcium phosphate building unit, [Ca(HPO4)3]4-, should only be present in small amounts under normal experimental conditions. However, the presence of an activation barrier for the removal of an HPO42- ion from this complex indicates that this species could be kinetically trapped. Aggregation pathways involving CaHPO4, [Ca(HPO4)2]2-, and [Ca(HPO4)3]4- complexes have been explored with the finding that dimerization is favorable up to a Ca/HPO4 ratio of 1:2.